2022
DOI: 10.1016/j.jbc.2022.101591
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of cyclic oligoadenylate binding to the transcription factor Csa3 outlines cross talk between type III and type I CRISPR systems

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 112 publications
(146 reference statements)
0
3
0
Order By: Relevance
“…The wide pool of functions inherent to the type III CRISPR-Cas systems -RNA targeting, second messenger signalling and the availability of large repertoire of ancillary proteins -raises the intriguing possibility that their functionality extends beyond immune defence 87 . An example of type III cOA signalling transcending direct antiviral defence is found in the CARF-containing transcription factor Csa3 from a co-occurring type I-A system, which seems to be involved in transcriptional regulation [118][119][120] . Certain type III CRISPR-Cas proteins secreted by the bacterial pathogen Mycobacterium tuberculosis were also shown to function as virulence factors 121 .…”
Section: Dissection Of Type III and Type Vi Crispr-casmentioning
confidence: 99%
“…The wide pool of functions inherent to the type III CRISPR-Cas systems -RNA targeting, second messenger signalling and the availability of large repertoire of ancillary proteins -raises the intriguing possibility that their functionality extends beyond immune defence 87 . An example of type III cOA signalling transcending direct antiviral defence is found in the CARF-containing transcription factor Csa3 from a co-occurring type I-A system, which seems to be involved in transcriptional regulation [118][119][120] . Certain type III CRISPR-Cas proteins secreted by the bacterial pathogen Mycobacterium tuberculosis were also shown to function as virulence factors 121 .…”
Section: Dissection Of Type III and Type Vi Crispr-casmentioning
confidence: 99%
“…The complete regulatory functions of these effectors appear to be very complex, but hints at cross-talk between type III and type I systems. It has been shown that Csa3 is involved in the regulation of type I CRISPR adaptation, as well as providing a feedback loop to type III interference [50][51][52][53][54]. Furthermore, Csa3-mediated activation of DNA repair genes has been demonstrated, indicating that the network of gene regulation by type III associated effectors might not be constricted to CRISPR-related genes [55].…”
Section: Coa-responsive Transcriptional Regulatormentioning
confidence: 99%
“…The complete regulatory functions of these effectors appear to be very complex, but hints to crosstalk between type III and type I systems. It has been shown that Csa3 is involved in the regulation of type I CRISPR adaptation, as well as providing a feedback loop to type III interference 134,218,[232][233][234] . Furthermore, Csa3-mediated activation of DNA repair genes has been demonstrated, indicating that the network of gene regulation by type III associated effectors might not be constricted to CRISPR-related genes 235 .…”
Section: Coa-responsive Transcriptional Regulatormentioning
confidence: 99%